Hubungan Antara Serangan Hama dan Penggunaan Pestisida: Pendekatan Analisis Ekonometrik pada Padi dan Kedelai - Joko Mariyono (Jurnal Perlindungan Tanaman Indonesia, 2002)
Pesticide is one of the pest control agents. Before concept of economic threshold was introduced, pesticide was used under scheduled method based on life cycle of insect pests. Therefore, pests damage was influenced by pesticide application, and resulting one-way relationship between pest attack and pesticide application. After the economic threshold concept was introduced as pest control strategy, the relationship becomes two-directions, namely pest attack is affected by pesticide application, and vice versa. Therefore, the simple relationship does not reflect the real condition. The unbiased relationship can be overcame by econometric approach called two stage least square, including new relevant independent variables. The objective of this study is determining the reversible relationship between pest attack and pesticide application. For this purpose, the time series data-containing pest attack level and pesticide application on rice and soybean during 1990–1998 were required. The result of analysis in rice indicated that the irreplaceable phenomenon that is increasing pest attack caused by rising pesticide application, but in soybean indicated common condition that is pest attack reduced when pesticide application increase. On the other hand, both pesticides application on rice and soybean were influenced by pests attack condition. Higher pest attack causes increasing pesticides application.